Pengaruh Tanaman Sela terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Kendek, Novita Cristine; Jamaluddin, Jamaluddin; Rauf, Reski Febyanti (Jurnal Pendidikan Teknologi Pertanian, 2024)
Cayenne pepper is a food ingredient that is liked by almost all people, including the people of Jeneponto. However, cayenne pepper production in 2021 will decline, one of the contributing factors is plant-disturbing organisms. The system that can be utilized is the organic farming system, one of the organic farming systems currently being developed is the companion planting system which is considered capable of increasing crop productivity. The aim of this study was to analyze the growth and yield of cayenne pepper (Capsicum frutescens L) with the sweet corn (Zea Mays L) companion planting system. The study was designed according to a completely randomized design with three treatments and three replications. The first treatment was cayenne pepper as a control (A), cayenne pepper and sweet corn or companion planting (B), and sweet corn as a control (C). The research was carried out for 56 WAP for cayenne pepper and for sweet corn it was carried out for 70 WAP. The observed variables were plant growth (plant height, cayenne pepper stem diameter, number of fruit, and fresh weight). From the results of the study it can be concluded that the use of companion planting systems can be utilized as a cropping system in the growth and increase in the production of cayenne pepper plants.